Willingness of Kansas farm managers to produce alternative cellulosic biofuel feedstocks: An analysis of adoption and initial acreage allocation - Lynes, Melissa K.; Bergtold, Jason S.; Williams, Jeffery R.; Fewell, Jason E. (My University, 2016)
This paper examines the likelihood that farm managers would be willing to harvest crop residue, or grow a dedicated annual or perennial bioenergy crop. In addition, factors affecting how many initial acres adopters would be willing to plant of a dedicated annual or perennial bioenergy crop are assessed. The study finds several factors affect farm managers' decisions to harvest crop residue, or grow annual or perennial bioenergy crops, as well as their potential initial acreage allocation decisions. These factors lead to several policy implications that should be tailored to the specific type of cellulosic bioenergy crop.
Keywords: Acreage Allocation; Annual Bioenergy Crop; Cellulosic Biofuel Feedstock; Crop Residue; Perennial Bioenergy Crop; Selection Model